Clinic–anatomical characteristic of the traffic–transport trauma in the megapolis environment First communication: the damage volume - S. O. Guryev; V. A. Kushnir (Клінічна хірургія)
Objective. To determine the damage volume as a significant component of clinical–anatomical characteristic of traumas in the injured persons, who have obtained the trauma as a consequence of the traffic–transport accidents in the megapolis environment.